The Mormyrid Optic Tectum Is a Topographic Interface for Active Electrolocation and Visual Sensing - Malou Zeymer; Gerhard von der Emde; Mario F. Wullimann (Frontiers in Neuroanatomy, 2018)
The African weakly electric fish Gnathonemus petersii is capable of cross-modal object recognition using its electric sense or vision. Thus, object features stored in the brain are accessible by multiple senses, either through connections between unisensory brain regions or because of multimodal representations in multisensory areas. Primary electrosensory information is processed in the medullary electrosensory lateral line lobe, which projects topographically to the lateral nucleus of the torus semicircularis (NL). Visual information reaches the optic tectum (TeO), which projects to various other brain regions. We investigated the neuroanatomical connections of these two major midbrain visual and electrosensory brain areas, focusing on the topographical relationship of interconnections between the two structures. Thus, the neural tracer DiI was injected systematically into different tectal quadrants, as well as into the NL. Tectal tracer injections revealed topographically organized retrograde and anterograde label in the NL. Rostral and caudal tectal regions were interconnected with rostral and caudal areas of the NL, respectively. However, dorsal and ventral tectal regions were represented in a roughly inverted fashion in NL, as dorsal tectal injections labeled ventral areas in NL and vice versa. In addition, tracer injections into TeO or NL revealed extensive inputs to both structures from ipsilateral (NL also contralateral) efferent basal cells in the valvula cerebelli; the NL furthermore projected back to the valvula. Additional tectal and NL connections were largely confirmatory to earlier studies. For example, the TeO received ipsilateral inputs from the central zone of the dorsal telencephalon, torus longitudinalis, nucleus isthmi, various tegmental, thalamic and pretectal nuclei, as well as other nuclei of the torus semicircularis. Also, the TeO projected to the dorsal preglomerular and dorsal posterior thalamic nuclei as well as to nuclei in the torus semicircularis and nucleus isthmi. Beyond the clear topographical relationship of NL and TeO interconnections established here, the known neurosensory upstream circuitry was used to suggest a model of how a defined spot in the peripheral sensory world comes to be represented in a common associated neural locus both in the NL and the TeO, thereby providing the neural substrate for cross-modal object recognition.